#### Answer

$ -i$

#### Work Step by Step

$i^23 = i^{20} \times i^3 = (i^4)^5 \times i^3 = 1^5 \times i^3 = 1 \times (-1)i = -i$

Published by
Pearson

ISBN 10:
013421742X

ISBN 13:
978-0-13421-742-0

$ -i$

$i^23 = i^{20} \times i^3 = (i^4)^5 \times i^3 = 1^5 \times i^3 = 1 \times (-1)i = -i$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.